Automação residencial em escala reduzida utilizando sistema microcontrolado - Bertoni, Lucas Andrey (2016)
The purpose of this work is to develop model to demonstrate the construction andoperation of a residential automation system using the Arduino Mega 2560 and otherelectronic components. The system can be configured according to the needs ofeach project, which in this case was control of lighting, alarm system, monitoring ofthe temperature of the pool water and opening and closing of the gate. An interfaceused for the control can be a web page or application that runs on an Androidoperating system beyond the control of some processes that can be done tophysically. App development requires specific knowledge of programming and C andC++ language fundamentals. The model of the residence was built in MDF with alower part to be stored the entire electrical part. The prototype worked properlyaccording to the project.